Anemia on Chronic Disease in Leprosy Before and After Completing Multi Drug Therapy - Ni Kadek Setyawati; Luh Made Mas Rusyati; I Gusti Ayu Agung Elis Indira; I Gusti Ayu Agung Praharsini; I Gusti Nyoman Darmaputra; I Gusti Ayu Agung Dwi Karmila (Green Publisher Indonesia, 2024)
Leprosy infection can cause anemia due to chronic disease (ACD). Multidrug therapy (MDT) for leprosy patients can overcome the infection. This study aims to determine the comparison in the incidence of ACD before and three months after MDT to leprosy patients at Prof. Dr. I G.N.G. Ngoerah Central General Hospital. A cross-sectional analytical observational study was conducted using secondary data from medical records of leprosy patients. A total of 142 samples were taken through total sampling. Data taken included gender, domicile, type of leprosy suffered, incidence of ACD, hemoglobin levels, and erythrocyte index before and three months after completing MDT leprosy therapy. Data analysis was carried out with SPSS version 21 using chi-square and paired t tests (dependent t-test), p value <0.05 means significant. The incidence of ACD was significantly higher before leprosy MDT therapy compared to 3 months after completing leprosy MDT therapy (49.3% vs. 16.2%; p value <0.001) with a prevalence ratio of 3.043 (2.021-4.584) CI95%. The mean hemoglobin levels, MCV, MCH, and MCHC levels 3 months after MDT leprosy therapy were significantly higher than before receiving MDT therapy (13.73 ± 1.47 vs. 12.40 ± 2.06 g/dL; p value <0.001), (88.18±7.22 vs. 84.07±9.55 fl; p value<0.001), (28.32±2.76 vs. 26.72±3.17 pg/cell; p value <0.001), (32.03±1.30 vs. 31.69±1.47%; p value<0.001). The incidence of ACD was significantly higher before MDT compared to 3 months after MDT. Mean hemoglobin, MCV, MCH, and MCHC levels were found to be significantly higher 3 months after MDT compared to before receiving MDT.